32.9k views
4 votes
Somebody help me out

Somebody help me out-example-1
User Neel Alex
by
5.5k points

2 Answers

7 votes
F(x)= 4(-5)^2 + (-5) -5
=4(25) -5-5
=100-5-5
=90
User Kiran Jadhav
by
5.1k points
6 votes


\longrightarrow{\green{90}}

Explanation:


f(x) = 4 {x}^(2) + x - 5

Now,


f( - 5) = 4( { - 5})^(2) + ( - 5) - 5 \\ \\ = 4 * 25 - 5 - 5 \\ \\ = 100 - 5 - 5 \\ \\ = 100 - 10 \\ \\ = 90

.........................................................

Note:-


\sf\purple{BODMAS\: rule.}

B = Brackets

O = Orders

D = Division

M = Multiplication

A = Addition

S = Subtraction

And,


\sf\red{(-\:x\:-)\:=\:+}


\sf\pink{(+\:x\:-)\:=\:-}

.........................................................


\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{♡}}}}}

User A Toll
by
4.9k points